Characterisation of Scientific Reasoning Levels Among Pedagogy Freshman Students: Challenges for Initial Teacher Education - Joglar-Campos, C; Rojas-Rojas, S; Tecpan-Flores, S (Centro de Informacion Tecnologica, 2020)
The aim of this study was to determine the relationship of the level of scientific reasoning (LSR) and pre-admission academic variables of 158 freshman students from five teaching programs in a Chilean public university. This study is part of a group of instruments that contribute to the national diagnosis for new requirements of law teaching career in Chile. The methodology was part of an ex post-facto transeccional causal-correlational study. The Lawson Test, adapted to the Chilean context, and multi-variable regression models were applied and designed to diagnose the LSR. The results showed the incidence in the LSR of the sex variable and pre-admission academic variables such scores in science and language in the Chilean university selection test (known as PSU). The results also showed alternative and inclusive access routes to teaching careers. It is concluded that level of scientific reasoning among first year students enrolled in teaching programs were primarily at transitional levels. © 2020. All rights Reserved